Two-photon excited deep-red and near-infrared emissive organic co-crystals - Yu Wang (Nature Portfolio, 2020)
Two-photon excited near-infrared fluorescence materials have garnered considerable attention because of their superior optical properties compared with other optical materials. Here, the authors use a convenient and efficient supramolecular approach to synthesize a two-photon excited near-infrared emissive co-crystalline material.